2017
DOI: 10.1016/j.foreco.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties in site prepared loblolly pine (Pinus taeda L.) stands 25 years after wet weather harvesting in the lower Atlantic coastal plain

Abstract: Harvesting traffic may alter soil properties and reduce forest productivity if soil disturbances are not mitigated. Logging operations were conducted during high soil moisture conditions on the South Carolina, USA coast to salvage timber and reduce wildfire potential following Hurricane Hugo in 1989. Long term study sites were established on wet pine flats to evaluate effects of primary skid trails and site preparation on soil properties and loblolly pine productivity. The experiment was analyzed as a split-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
“…The incorporation of surface OM during bedding operations initially increases mineral soil C and N concentrations (Maier et al, 2012), but McKee and Shoulders (1974) reported soil OM concentrations were significantly lower 8 yr after bedding. Neaves et al (2017) also found a similar reduction in soil C content 25 yr after soil bedding. Such long‐term C reductions in bedded soils are likely caused by increased OM decomposition by soil microorganisms, such as was shown in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Increased soil volume above the water table, and the physical mixing of surface OM with mineral soil by bedding equipment, improves the soil macropore to micropore ratio, lowers bulk density, increases N availability, and most importantly, increases soil oxygen levels in poorly‐drained soils (Kelting et al, 2000; Neaves et al, 2017). The average height of the double beds in our study was 30 cm, but varied from a minimum height of 23 cm to a maximum of 43 cm above the original wetland soil surface (P. Dougherty, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been concern about this site preparation method, especially with respect to hydrology, C storage, and nutrient cycling, it has been considered inconsequential for many wetland functions (Harms et al 1998). Studies in Michigan and South Carolina (Neaves et al 2017b) on soil property responses to bedding and plantation establishment have shown disturbance effects to be short term (e.g., <20 years).…”
Section: Forest Managementmentioning
confidence: 99%